weIMPUTE: a user-friendly web-based genotype imputation platform - Li, Mingliang; Li, Zhuo; Liu, Defu; Li, Qi; Hu, Xiaodong; Yu, Jun; Lin, Jian; Bi, Chunguang; Ye, Guanshi; Yu, Helong; Tang, You (Frontiers in Genetics, 2025)
BackgroundGenotype imputation is a critical preprocessing step in genome-wide association studies (GWAS), enhancing statistical power for detecting associated single nucleotide polymorphisms (SNPs) by increasing marker size.ResultsIn response to the needs of researchers seeking user-friendly graphical tools for imputation without requiring informatics or computer expertise, we have developed weIMPUTE, a web-based imputation graphical user interface (GUI). Unlike existing genotype imputation software, weIMPUTE supports multiple imputation software, including SHAPEIT, Eagle, Minimac4, Beagle, and IMPUTE2, while encompassing the entire workflow, from quality control to data format conversion. This comprehensive platform enables both novices and experienced users to readily perform imputation tasks. For reference genotype data owners, weIMPUTE can be installed on a server or workstation, facilitating web-based imputation services without data sharing.ConclusionweIMPUTE represents a versatile imputation solution for researchers across various fields, offering the flexibility to create personalized imputation servers on different operating systems.